Prevalence and Factors associated with sickness absenteeism among Pharmaceutical Industrial workers of Hyderabad, India - Bala, Sudha; B, Rajiv Kumar; Pandve, Harshal (Asian Journal of Medical Sciences, 2021)
Background: Sickness absenteeism is a potential epidemiological issue leading to loss of productivity in addition to increasing the cost of health care and provides a major tool in enhancing occupational health care preventive strategies. Aim and Objectives: To determine the prevalence of sickness absenteeism and their associated factors among Industrial Workers of Pharmaceutical Manufacturing industries in Hyderabad. Materials and Methods: A cross sectional study was taken up among 160 Workers at two Pharmaceutical Manufacturing companies in Hyderabad using simple random sampling technique. Data included Individual, Occupational and Organizational factors influencing their sickness absenteeism and general health conditions in the past six months through camp based approach. Data was analysed using descriptive statistics and multinomial logistic regression analysis to predict the variables associated with the outcome. Results: The prevalence of sickness absenteeism was found among 19% of the workers. Common causes were due to sickness among 25(84%) and social responsibilities among 5(16%). On multinomial logistic regression analysis- poor superior relationships, poor co-workers relationship and high mental stress were found to be significant. Conclusion: Sickness absenteeism was found to be high which can be reduced by improving relationships with superiors and co-workers and also by reducing mental stress among the workers.